EZR–ROS1 rearrangement as a novel mechanism of acquired resistance to EGFR-TKIs in NSCLC: a case report and literature review - Hu, Jia; Hui, Fu; Jiang, Yiqing; Zhang, Yi; Li, Luxin; Yu, Mingxin; Chen, Yue; Ding, Yanhong; Zhang, Xuede (Frontiers in Immunology, 2026)
ROS1 rearrangement is a rare mechanism of acquired resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), with an incidence of less than 1% in non-small cell lung cancer (NSCLC). However, the clinical characteristics and therapeutic strategies for patients who develop ROS1 rearrangement after resistance to EGFR-TKIs remain undefined. Here, we describe the first case of EGFR-TKIs resistance caused by the EZR exon 10–ROS1 exon 34 rearrangement. This case highlights ROS1 rearrangement as a rare but targetable mechanism of acquired resistance to EGFR-TKIs. Additionally, we conducted a comprehensive review of previously reported cases of other ROS1 rearrangements occurring after EGFR-TKIs resistance in NSCLC. Our analysis reveals that this rare mutation shares notable clinical similarities with primary ROS1 rearrangement in certain characteristics. However, it exhibits significant differences in fusion partner distribution and co-mutation frequency compared to the primary ROS1 rearrangement. The efficacy of crizotinib in this molecular subset demonstrates favorable clinical outcomes. Furthermore, considering the relatively high prevalence of ROS1 co-mutations with other genetic alterations in these cases, multi-targeted combination therapy may represent a promising therapeutic strategy for this distinct patient population.